MODEL EMPIRIS MEMBANGUN KESETIAAN PELANGGAN BERBASIS KUALITAS PELAYANAN DENGAN MEDIASI KUALITAS HUBUNGAN PADA INDUSTRI RITEL BERBASIS JEJARING MINIMARKET - Mohammad Dimyati; Mochammad Farid Afandi (Jurnal Manajemen dan Pemasaran Jasa, 2018)
The objective of this research is to analysis the direct effect of service quality on relationship quality and customer loyalty, the direct effect of relationship quality on customer loyalty, and indirect effect of service quality on customer loyalty mediated by relationship quality. This research also aims to build an empirical model of customer loyalty based on service quality, mediated by relationship quality in the networked minimarkets in Besuki Raya Region, East Java Province, Indonesia. This is a confirmatory research and also explanatory research with population consists of customers of the networked minimarkets located in 5 areas in Besuki Raya. Region, i.e., Banyuwangi, Jember, Bondowoso, Situbondo, Lumajang. This research used purposive sampling method by distributing questionnaires to respondents. The total of 140 respondents used as the sample. The results show that the improvement of service quality directly increases relationship quality, the improvement of relationship quality directly increases customer loyalty, and that relationship quality has a significant and important influence in mediating the effect of service quality on customer loyalty. However, this research proves that the improvement of service quality has no direct effect on increasing customer loyalty.